Heart rate passivity of cerebral tissue oxygenation is associated with predictors of poor outcome in preterm infants. (1st August 2014) - Mitra, S; Czosnyka, M; Smielewski, P; O'Reilly, H; Brady, K; Austin, T
Abstract Aim Near‐infrared spectroscopy (NIRS) and transcranial Doppler (TCD) allow non‐invasive assessment of cerebral haemodynamics. We assessed cerebrovascular reactivity in preterm infants by investigating the relationship between NIRS‐ and TCD‐derived indices and correlating them with severity of clinical illness. Methods We recorded the NIRS‐derived cerebral tissue oxygenation index (TOI) and TCD‐derived flow velocity (Fv), along with other physiological variables. Moving correlation coefficients between measurements of cerebral perfusion (TOI, Fv) and heart rate were calculated. We presumed that positivity of these correlation coefficients – tissue oxygenation heart rate reactivity index (TOHRx) and flow velocity heart rate reactivity index (FvHRx) – would indicate a direct relationship between cerebral perfusion and cardiac output representing impaired cerebrovascular autoregulation. Results We studied 31 preterm infants at a median age of 2 days, born at a median gestational age of 26 + 1 weeks. TOHRx was significantly correlated with gestational age (R = −0.57, p = 0.007), birth weight (R = −0.58, p = 0.006) and the Clinical Risk Index for Babies II (R = 0.55, p = 0.0014). TOHRx and FvHRx were significantly correlated (R = 0.39, p = 0.028). Conclusion Heart rate has a key influence on cerebral haemodynamics in preterm infants, and TOHRx may be of diagnostic value in identifying impaired cerebrovascular reactivity leading to adverse clinical outcome.